Rancang Bangun Sistem Penjualan Makanan Berbasis Web di Rumah Makan Saung Tiga - Syarif Saputra; Yoseph Kawena Hayon; Jupron Jupron (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
The rapid advancement of information technology has significantly impacted the culinary business sector, particularly in improving service quality and operational efficiency. Saung Tiga Restaurant, located in Sawangan, Depok, West Java, still relies on a manual ordering process that frequently leads to recording errors, service delays during peak hours, and difficulties in generating accurate sales reports. This study aims to design and develop a web-based food ordering system using the Waterfall development method. The system was built with the Laravel framework, Blade Template Engine for the backend, Bootstrap for the frontend, and MySQL as the database. The system features digital menu management, an online ordering module with a shopping cart, table reservation with double-booking prevention, real-time order status management through an admin dashboard, and daily and monthly sales statistics. System testing was conducted using the Black Box Testing method across 19 test scenarios covering all major functional features. The results showed a 100% success rate, indicating that the system fully meets the specified functional requirements and is ready for implementation at Saung Tiga Restaurant.